Planted mangroves cap toxic petroleum-contaminated sediments. (October 2021) - Waryszak, Paweł; Palacios, Maria M.; Carnell, Paul E.; Yilmaz, I. Noyan; Macreadie, Peter I.
Abstract: Mangroves are known to provide many ecosystem services, however there is little information on their potential role to cap and immobilise toxic levels of total petroleum hydrocarbons (TPH). Using an Australian case study, we investigated the capacity of planted mangroves ( Avicennia marina ) to immobilise TPH within a small embayment (Stony Creek, Victoria, Australia) subjected to minor oil spills throughout the 1980s. Mangroves were planted on the oil rich strata in 1984 to rehabilitate the site. Currently the area is covered with a dense mangrove forest. One-meter-long sediment cores revealed that mangroves have formed a thick (up to 30 cm) organic layer above the TPH-contaminated sediments, accumulating on average 6.6 mm of sediment per year. Mean TPH levels below this organic layer (30–50 cm) are extremely toxic (30, 441.6 mg kg −1 ), exceeding safety thresholds up to 220-fold which is eight times higher when compared to top layer (0–10 cm). Highlights: Mangroves represent ability to immobilise sediments contaminated by total petroleum hydrocarbons (TPH) Planted mangroves immobilised TPH-contaminated sediments that exceeded toxicity thresholds by up to 220-fold Capping the TPH-contaminated sediments is linked to ability of mangroves to grow and accumulate sediments above contaminated sediments Mangroves in this study accumulated relatively high organic matter content within rhizosphere (~16.6% in top 30 cm).